Optimal operation of Combined Cooling Heat and Power (CCHP) systems in future energy networks - Chai, Yiting (Nanyang Technological University, 2019)
There has been much heard that energy consumption worldwide is expected to grow. In order to pursue higher energy efficiency, it is necessary to obtain the maximum gain on energy resources. Combined cooling heat and power (CCHP) energy system, which is the simultaneous production of electric and thermal energy from fuel source, is found widespread adoption. The objective of this project is to propose an optimal operation method of CCHP-based microgrid. In this project, the multi-energy microgrid consists of controllable generators, such as micro turbine, fuel cell, electric chiller and boiler; uncontrollable generators, such as wind turbine and photovoltaic cell; and energy storage systems, such as electric energy storage and thermal energy storage. Optimization method is approached by YALMIP, which is a toolbox of MATLAB, as mixed-integer linear programming problems. The optimal result should lead to minimal daily operation costs while fulfilling electric and thermal energy demands of users. It should also enhance the dispatch flexibility of supplying electric energy and thermal energy according to daily energy market. Practical cases are studied to compare the effectiveness of the proposed method with the other two dispatch methods. Simulation results have demonstrated the feasibility of the proposed method.